2020
DOI: 10.1186/s12889-019-8127-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the healthcare experiences and needs of African immigrants in the United States: a scoping review

Abstract: Background: Africans immigrants in the United States are the least-studied immigrant group, despite the research and policy efforts to address health disparities within immigrant communities. Although their healthcare experiences and needs are unique, they are often included in the "black" category, along with other phenotypically-similar groups. This process makes utilizing research data to make critical healthcare decisions specifically targeting African immigrants, difficult. The purpose of this Scoping Rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 77 publications
1
60
0
Order By: Relevance
“…Health is a human right that can influence the ability to enjoy other rights. However, many African migrants experience health challenges upon settlement in a new country [ 8 , 9 ]. Pre-migration factors (e.g., experience of trauma) and post-migration challenges (e.g., access to health care) contribute to the health of immigrants in destination countries [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health is a human right that can influence the ability to enjoy other rights. However, many African migrants experience health challenges upon settlement in a new country [ 8 , 9 ]. Pre-migration factors (e.g., experience of trauma) and post-migration challenges (e.g., access to health care) contribute to the health of immigrants in destination countries [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-migration factors (e.g., experience of trauma) and post-migration challenges (e.g., access to health care) contribute to the health of immigrants in destination countries [ 1 , 10 ]. A scoping review that included 14 articles found that culture, religious beliefs, linguistic barriers, and barriers accessing health care contributed to the health of African immigrants in the United States [ 8 ]. Barriers to access to health care for this population include cost, health system complexity, lack of culturally competent health providers, long wait times, and discrimination [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to healthcare remains a major obstacle across immigrant communities [ 14 , 15 ]. Factors attributed to these barriers in healthcare access include interconnected structural and individual-level barriers, including ineligibility for certain healthcare programs [ 16 ], limited in-language support for culturally appropriate healthcare services [ 17 ], lack of knowledge of the healthcare system [ 18 ], distrust of the U.S. healthcare system [ 19 ] and, particularly among undocumented immigrants, fears related to deportation due to policies linking documentation status with use of public services [ 15 , 20 ]. Access-related issues often intersect with other barriers to healthcare utilization and health behaviors among immigrants, including specific customs or unique cultural or religious understandings of health and disease [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors attributed to these barriers in healthcare access include interconnected structural and individual-level barriers, including ineligibility for certain healthcare programs [ 16 ], limited in-language support for culturally appropriate healthcare services [ 17 ], lack of knowledge of the healthcare system [ 18 ], distrust of the U.S. healthcare system [ 19 ] and, particularly among undocumented immigrants, fears related to deportation due to policies linking documentation status with use of public services [ 15 , 20 ]. Access-related issues often intersect with other barriers to healthcare utilization and health behaviors among immigrants, including specific customs or unique cultural or religious understandings of health and disease [ 19 , 21 ]. These various influences also underpin hypertension outcomes among immigrants; U.S. immigrants are more likely to be unaware of their hypertension [ 22 ], have undiagnosed or uncontrolled hypertension [ 23 ], and display lower treatment rates of hypertension, particularly among those without a usual source of care or health insurance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%